Designing an ICT tooling platform to support the needs of SMEs in business model innovation - Mark de Reuver; Astrid Tarkus; Timber Haaker; Gert Breitfuss; Melissa Roelfsema; Ruud Kosman; Marikka Heikkilä (Austria, 2022)
The relevance of Business model innovation (BMI) to survival and competitiveness of companies is largely acknowledged by academia and industry. Still, a recent study by Bouwman et al (2016) showed that 37% of Europe’s small and medium sized companies (SMEs) are engaged in BM Innovation. This means that almost two thirds of the SMEs do not change their business logic, thus staying within their familiar comfort zone. This can be fine for some, but many more SMEs will need to adjust and innovate their business model as the world changes around them especially due to digitalisation. Moreover, very few SMEs use formal methods to improve their BM - of those SMEs that do BM Innovation, only 19% make use of formal methods (Bouwman et al., 2016). This raises a question whether it is possible to support the BM innovation of SMEs by providing them tools that fit their strategic aims and practical BMI needs.
In this paper, we present two design cycles for an online platform with ICT-enabled tooling that supports business model innovation by SMEs. The platform connects the needs of the SMEs regarding BMI with tools that can help to solve those needs and questions. The needs are derived from our earlier case study work (Heikkilä et al. 2016), showing typical BMI patterns of the SMEs needs - labelled as ‘I want to’s - about what an entrepreneur wants to achieve with business model innovation. The platform provides sets of integrated tools that can answer the typical ‘I want to’ questions that SMEs have with innovating their business models
Exploring a changing view on organizing value creation: Developing New Business Models